Intelligent Computing System to Predict Vocational High School Student Learning Achievement Using Naïve Bayes Algorithm - Herlambang, Admaja Dwi; Wijoyo, Satrio Hadi; Rachmadi, Aditya (Journal of Information Technology and Computer Science, 2019)
Vocational High School with ICT major need an intelligent computing system that could predict the student learning achievement. The system used fifteen achievement indicators and Naïve Bayes algorithm in data processing. Testing on student achievement data produces the conclusion that is the highest intelligent accuracy values in 53% with lowest accuracy value in 48% based on Naïve Bayes algorithm processing. The result of mining process using Naïve Bayes algorithm can be used to classify the 3rd year student achievement to five categories. These categories are Very Good, Good, Fair, Poor, and Failed. The system testing result showed that this intelligent computing system function was fitted with Vocational High School’s system requirement, system design, and system implementation.